Examining Students’ Motivation and Attitudes towards Mathematics - Nagyová Lehocká, Zuzana; Kmetová, Mária (TEM Journal, 2025)
The article aims to provide a brief overview of students’ possible motivations and attitudes, which may be decisive for their achievement in one or another subject, which in this case is mathematics. A scale questionnaire has been developed to understand teenagers’ interest in mathematics and distinguish their motivations. Next, the research is presented based on these questionnaires, analysing the answers in terms of both student grades and gender differences. The research primarily examined the attitudes of 13-15-year-old students toward mathematics.